(untitled) (Olhar de Professor, 2024)
This work aim to relate a experience of tutoring in the subject Reading and Production of Genres II, in the Language Course - Portuguese Language, at the Federal University of Campina Grande, Cajazeiras campus, during the Extraordinary Academic Regime at the 2020.3. The report highlights points that marked this subject, considering the peculiarities that marked the return to the presence of classes. To this end, we reflect on distance learning and the associations with remote teaching; discuss the configuration of this teaching that we are aware of today; and we highlight the of Monitoring Programs in the teaching and learning process. The work is characterized of the ex-post-facto, descriptive and qualitative. We observed that, during the weeks in which the subject’s activities took place, the participation forums made it possible to have moments of asynchronous interaction, and the production of texts contributed to the construction of learning in the remote modality.